On Ordinary, Linear q-Difference Equations, with Applications to q-Sato Theory. (23rd February 2015) - Ernst, Thomas
Abstract : The purpose of this paper is to develop the theory of ordinary, linearq -difference equations, in particular the homogeneous case; we show that there are many similarities to differential equations. In the second part we study the applications to aq -analogue of Sato theory. Theq -Schur polynomials act as basis function, similar toq -Appell polynomials. The Wardq -addition plays a crucial role as operation for the function argument in the matrixq -exponential and for theq -Schur polynomials.